Formação Docente: o Programa de Residência Pedagógica no Curso de Ciências Biológicas da UFC - Moreira, Thaís Borges (2020)
One of the biggest challenges in improving the teaching quality in the context of basic education is the establishment of a solid foundation in initial teacher education. Public policies that encourage this initial training are present, as in the Pedagogical Residency Program (PRP). As it is a new program, research on it is fundamental relevance, given that, in times of budget cuts, especially in the educational area, it is necessary to show how such programs can contribute to strengthen the initial training of teachers. Thus, the main objective of this investigation was to analyze how the Pedagogical Residence can contributes to the initial training of future biology teachers. In addition, it was also intended, as specific objectives, 1. Understand the organization of activities developed in each eschool; 2 Understand how residents perceive their participation in the PRP; 3. Analyze how residents interrelate with school and institutional agents. Throughout this research, it was first presented the scientific life trajectory of the author, and then, how the State of the Question was constituted, where through it, it was better understood what was in the literature to delimit the themes to be addressed. As for the methodology, a qualitative approach was chosen, with the application of a semi-structured questionnaire and the use of the focal group technique for data collection. Data analysis was done through Discursive Textual Analysis, with immersion in the corpus of the work, categories creation and metatexts construction. Through the results found, it was realized the importance of the PRP for the initial training of residents, where they discussed the challenges experienced, the contributions, the relationship of residents with school agents, tutors and other factors related to initial training, such as the subjects during graduation. Thus, it can be concluded that the Pedagogical Residence still has factors to be adjusted, but, in fact, the residents face positively the participation in the Program.